Vitamin E ameliorates testicular histological features and androgen binding protein levels in testicle of rats induced by allethrin - Sukmawati, Yofa; Arisanty, Dessy; Tofrizal, Alimuddin; Amir, Arni (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This study aims to determine the ameliorative effect of vitamin E (vit E) on histological features and androgen binding protein (ABP) levels in rats induced by allethrin. Materials and Methods: Thirty sexually mature male Wistar rats weighing between 200 and 300 gm, and aging 3 months were taken for this study and were divided into three groups: negative control (NC), positive control (PC), and treatment (T) groups. The PC and T groups were induced by allethrin 12 h per day for 31 days; however, only the T group was given vit E orally at 1 ml/gm body weight (BW) each day for 14 days. The paraffin block method was used to measure tubules’ diameter, thickness of the seminiferous epithelial layer, and Sertoli cell number. The ABP levels were measured by enzyme-linked immunosorbent assay. Results: The results showed that vit E gave significant effect (p < 0.05) on tubular diameter at NC 123.67 ± 12.77, PC 147.16 ± 10.64, and T 130.08 ± 10.00; tubular epithelial thickness at NC 33.55 ± 3.21, PC 30.02 ± 1.53, and T 32.96 ± 2.81; Sertoli cells number at NC 55.48 ± 5.9, PC 43.84 ± 3.77, and T 53.44 ± 4.26; and ABP levels at NC 72.35 ± 39.06, PC 38, 48 ± 18.78, and T 86.10 ± 35.77, respectively. Conclusion: This study concludes that vit E has an ameliorative effect against the toxic effects of allethrin at testicular histological features and ABP levels. J. Adv. Vet. Anim. Res., 6(4): 486-491, December 2019